POLITIK DAN PEREMPUAN DI INDONESIA PASCA REFORMASI - Indra Fauzan (Jurnal Ilmiah Mimbar Demokrasi, 2017)
Women in the political context of Indonesia has a very significant role, because the position of women in politics in Indonesia not yet well established and sometimes even impressed marginalized because of the position of women in politics is always behind man. This can be seen in various positions in political parties, political organizations and even in Parliament though. This indicates that women's political participation is still very limited so that the position of women in politics in Indonesia is still very weak, so in need of a strategy to increase women's political participation in Indonesia either from the lowest to the highest rank. Although there is affirmative action to increase women's political participation in politics but it does not guarantee that the political position of women to be equal to men colleagues Because there are not many women who want and memimiliki opportunity for a career and strive in the path of politics. Many problems encountered principally in Indonesian culture. This study will explore how women's political participation in the political context in Indonesia and is expected to add to the treasures of female political discourse itself.